Penerapan Tekonologi Website dan Pembuatan Manajemen Usaha Berkelanjutan pada Kelompok Ternak Domba untuk Meningkatkan Kesejahteraan Masyarakat - Ichwani, Arief; Indrawan, Heronimus Erwin; Uddin, Badie (JPM: Jurnal Pengabdian Masyarakat, 2025)
In the era of digital transformation, many Micro, Small, and Medium Enterprises (MSMEs) still face various challenges in adopting digital technology, especially in marketing and business management aspects. The Sauyunan Sheep Farming Business Group (Kelompok Usaha Peternakan Domba Sauyunan) is an MSME engaged in sheep farming, located at Kp. Seketando RT 001 RW 013, Cangkorah Village, Batujajar District, West Bandung Regency (KBB). The main problem faced by the Sauyunan Sheep Farming Group is that business management remains traditional. These limitations include the absence of long-term business planning (blue print), incomplete and immature organizational management, non-standardized financial recording, and marketing reach limited to conventional local markets. This Community Service (Pengabdian Kepada Masyarakat or PKM) activity aims to transform partner business management through digitalization and the strengthening of sustainable business management. The implementation method uses a participatory approach comprising socialization, training, technology implementation, evaluation, and intensive mentoring. The PKM activity was carried out in three sessions involving 25 participants consisting of a team of lecturers, Esa Unggul University students, and livestock group members. The results of this activity regarding the business management aspect are the compilation of a business blue print document covering vision, mission, and strategic targets from the short to long term; the formation of a functional organizational structure for HR optimization; the establishment of customer management standards; and the partners' capability in financial recording and calculation. Meanwhile, the results regarding the business digitalization aspect include the availability of an official e-commerce website integrated with the Sauyunan Sheep Group’s social media, and the partners' capability to utilize it effectively for marketing and sales digitalization. This has had a positive impact by expanding customer reach, increasing sales turnover, and improving the welfare of group members sustainably